2000
DOI: 10.1007/s11886-000-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Beta-carotene, vitamin C, and vitamin E and cardiovascular diseases

Abstract: Observational studies have shown an inverse relationship between consumption of fruits and vegetables high in beta-carotene, vitamins C and E, and ischemic heart disease (IHD) and stroke. In large observational studies, beta- carotene reduced the risk of IHD events in men, particularly in smokers. In contrast, four large randomized trials did not reveal a reduction in cardiovascular events with beta-carotene use, and may, in fact, increase IHD and total mortality in male smokers. There have been only a few lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Despite expectations, randomized trials have provided limited evidence for the role of isolated nutrients, such as are found in Mediterranean foods, in the prevention of cardiovascular disease or mortality. With the exception of n-3 and other polyunsaturated fatty acids, clinical trials testing the efficacy of antioxidants, such as beta-carotene and vitamin E, have reported no protective effects on cardiovascular disease (GISSI-Prevenzione Investigators, 1999;Marchioli, 1999Marchioli, , 2001Dagenais et al, 2000;Alpha-Tocopherol, Beta Carotene Cancer Prevention Study Group, 1994;Omenn, 1995;Hennekens et al, 1996;Omenn et al, 1996;HOPE Study Investigators, 2000, Collaborative Group of the Primary Prevention Project, 2001Brown et al, 2001). For example, the recently completed Heart Prevention Study (MRC/BHF Heart Protection Study Collaborative Group, 1999) found that a cocktail of antioxidant vitamins had no benefit in patients at high risk of cardiovascular death, even with a sample size of over 20 000.…”
Section: Discussionmentioning
confidence: 99%
“…Despite expectations, randomized trials have provided limited evidence for the role of isolated nutrients, such as are found in Mediterranean foods, in the prevention of cardiovascular disease or mortality. With the exception of n-3 and other polyunsaturated fatty acids, clinical trials testing the efficacy of antioxidants, such as beta-carotene and vitamin E, have reported no protective effects on cardiovascular disease (GISSI-Prevenzione Investigators, 1999;Marchioli, 1999Marchioli, , 2001Dagenais et al, 2000;Alpha-Tocopherol, Beta Carotene Cancer Prevention Study Group, 1994;Omenn, 1995;Hennekens et al, 1996;Omenn et al, 1996;HOPE Study Investigators, 2000, Collaborative Group of the Primary Prevention Project, 2001Brown et al, 2001). For example, the recently completed Heart Prevention Study (MRC/BHF Heart Protection Study Collaborative Group, 1999) found that a cocktail of antioxidant vitamins had no benefit in patients at high risk of cardiovascular death, even with a sample size of over 20 000.…”
Section: Discussionmentioning
confidence: 99%
“…We used 14 pro- and anti-oxidant factors that were selected a priori based on previous research [32–42], as well as data-based, a priori tertile cut-points for continuous variables to minimize subjective categorization, which is a general problem with scores for attempting to describe complex processes. In this study, mortality and cause of death were adjudicated by expert clinicians using death certificates, medical records from recent hospitalizations, and interviews with proxies, a methodological feature that helped decrease outcome misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Vast experimental evidence supports the notion that ROS play a role in promoting functional and structural injury in the long term and that antioxidant strategy is beneficial in several models of cardiovascular and renal disease (10,12,44,49). On the other hand, evidence derived from clinical studies is not conclusive, since a few studies have shown benefits from antioxidants but several trials have shown mixed results (13,47). The reasons for disparate results in experimental and clinical studies are not clear, but might be related to the type of antioxidant strategy, timing, and length of its use, or the type, severity, and stage of the disease.…”
Section: Discussionmentioning
confidence: 99%